FAMILY VALUES AND THE REGULATION OF LABOR. Issue 4 (3rd April 2015) - Alesina, Alberto; Algan, Yann; Cahuc, Pierre; Giuliano, Paola
Abstract To be efficient, flexible labor markets require geographically mobile workers. Otherwise firms can take advantage of workers' immobility and extract rents at their expense. In cultures with strong family ties, moving away from home is costly. Thus, to limit the rents of firms and to avoid moving, individuals with strong family ties rationally choose regulated labor markets, even though regulation generates higher unemployment and lower incomes. Empirically, we find that individuals who inherit stronger family ties are less mobile, have lower wages and higher unemployment, and support more stringent labor market regulations. We find a positive association between labor market rigidities at the beginning of the 21st century and family values prevailing before World War II, and between family structures in the Middle Ages and current desire for labor market regulation. Both results suggest that labor market regulations have deep cultural roots.